Groundwater Study in Limestone Area using Geophysical Methods: https://doi.org/10.69692/SUJMRD0802290 - SOMPASERTH, Sackxay; SINGSOUPHO, Sounthone; XOUNSOUNDAO, Thiengsamone; XAYSOMBATH, Soukdalay; THAVIXAY , Phaythoun; VOLACHACK, Nyphonh (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
Applied geophysics is important for groundwater investigation. Drilling groundwater boreholes without geophysical survey is probably unsuccessful. Meth district, Vientiane Province is the study site due to the most area coving with limestone area. The objective of this study is to define the groundwater model including location, depth and thickness of aquifer using 2D resistivity measurement, groundwater flow direction using self potential measurement. In addition, basic groundwater quality (pH, Ec and TDS) is also defended. 2D-Electrical Resistivity Tomography (2D-ERT) meauremnt using Wenner arrray was conduced for 2 lines with 300m of length and a varying from a=5m to 100m. Self Potential measurment using fixed-base method was performed for 3 lines with 300m of leng and 10m spacing of each measurming point. The results of the 2D-ERT show that low resistivity from 10 to 80 ohm-m at depth of 20-28m interpreted as aquifer layer. But high resistivity from 200 to 600 ohm-m is resulted from base rock. The volage from SP measurment varying ranging from -14 to 24 mV can be defined the flowdirection from NE-SW direction. It is correlating with the topography of the area. The result of physical properties from 3 samples show that pH=6.8±0.5, Ec=480±115 mS/cm, and TDS=343.3±80.2 mg/l. are under the standard values issued by Minstry of Health, Laos.The water qulity is good . The geophysical survey is effective usful methods for groundwater suvey due to low cost and rapid for survey. Geophysical result could be intributed to comunity, government sectors in order to high effective management the groundwtater resources in the future. Moreover, the data is also usfull for researcher and students.